Consumer Perception and Expectation on Sharia Bank’s Product Differentiator a Study for Bank DKI Syariah - Safri, Amin; Hasman, Inda D.; Soeriaatmadja, Tubagus Hanafi (Bina Nusantara University, 2012)
The aim of this study is to find some uniqueness of Sharia aspects which are expected by consumer to be embedded into a Sharia Banking’s product. This study will analyze Sharia Banking Consumer perception attitudes toward Sharia funding product in Indonesia by using the sources of research data from a well known regional Sharia retail bank in Indonesia, Bank DKI Syariah which is keen to grow their funding business as much as possible. The project research’s output is expected to recommends Bank DKI Syariah as the subject of this study, to initiate any further research and review their strategic business plan by using this particular consumer perception result on the raised issues. The finding hopefully can eventually be utilized in forming new Sharia Banking product models that are more sustainable to support the industry trend to a leading position in the new economic era of Islamic finance in Indonesia.